PENYELIDIKAN GEOLISTRIK MENGGUNAKAN KONFIGURASI SCHLUMBERGER TERHADAP POTENSI AMBLESAN DAERAH PONJONG, GUNUNG KIDUL - Rizqi, Al Hussein Flowers; Yudhana, Waskita Murti Bambang (KURVATEK, 2020)
Administratively, the research area is included in Ponjong Subdistrict, Gunung Kidul Regency, Special Region of Yogyakarta. Geographically, it’s located in 07°56’30" - 08°1’0" East Longitude and 110°42’30" - 110°46’0" South Latitude. Several subsidences were occurred in Ponjong, Gunung Kidul in 2018. This study is aimed to determine the subsurface stratigraphy and analyze the depth of rocks layer which has the potential of subsidence (sinkhole) based on the value of rocks resistivity in Ponjong area. Resistivity was measured by geoelectrical method by appllying Schlumberger configuration. As a result, the study areas indicates that the most potential area having sinkhole are composed of lithology of carbonate rocks from Wonosari Formation (crystaline limestone and chalky limestone). Those are in the Asem Lulang village in showed small value of rock resistivity, about 0.1 to <1 (Ωm) at the depth of 15 to 63 meter and more than 123 meter. If it comparated to the village of Sawahombo and Kenteng village, the result showed that relative potential area of subsidence (sinkhole) only at shallow depth and nearly to the surface which is only 10 to 15 meter from surface.Keywords: geoelectric, ponjong, Schlumberger, Sinkhole, Wonosari